2019
DOI: 10.1039/c9sc02609f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical C–H oxygenation and alcohol dehydrogenation involving Fe-oxo species using water as the oxygen source

Abstract: The well-known [(TAML)Fe(OH2)]− complex undergoes proton-coupled oxidation to an Fe-oxo species that supports electrochemical C–H oxidation and alcohol dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 80 publications
2
61
0
Order By: Relevance
“…With the optimized reaction conditions defined, we set out to explore the scope of the electrooxidation of methylarenes. Notably, the site-selectivity was not significantly affected by introducing a phenyl (3), bromo (4), or cyano group (5) at C5, or by varying the substituent on N1 (6-9) or C2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) of the C4,C6-dimethylated benzimidazole substrate (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the optimized reaction conditions defined, we set out to explore the scope of the electrooxidation of methylarenes. Notably, the site-selectivity was not significantly affected by introducing a phenyl (3), bromo (4), or cyano group (5) at C5, or by varying the substituent on N1 (6-9) or C2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) of the C4,C6-dimethylated benzimidazole substrate (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…1a). As an alternative to chemical oxidation, electrooxidation eliminates the use of stoichiometric chemical oxidants and is attracting increasing interests [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . Notably, electrooxidation of electron-rich toluene derivatives to substituted benzaldehydes has been applied in the industrial production of panisaldehyde and 3,4,5-trimethoxybenzaldehyde [27][28][29] .…”
mentioning
confidence: 99%
“…Iron(III/IV)r eductionp otentials of the first series of TAML activators (TAMLs 1 of first generation [8] )o btainedb yc yclicv oltammetryi na cetonitrile were reported ad ecadea go by our group [9] and recentlyb yo thers. [10] In most cases, ac omplex speciation of iron(IV) TAMLsi nw ater precludes accurated etermination of reduction potentials using cyclicv oltammetry.T he Fe III/IV and Fe IV/V values were obtained under basicc onditions using differential pulse voltammetry. [11] Ar ecentelectrochemical studyof" beheaded"T AML activator 3 revealed that itsF e III/IV andF e IV/V reduction potentials arem easurable by cyclic voltammetryi nabroad pH range.…”
Section: Introductionmentioning
confidence: 99%
“…substrates having C-H bonds with BDE less than 90 kcal mol À1 . 34 In this electrocatalytic approach, the breadth of reactivity demonstrated with the Fe-bTAML complex is not achieved due to the oxidative self-decomposition of the prototype Fe-TAML catalyst under the bulk electrolysis conditions, which limits the catalyst lifetime. In addition, the instability of oxoiron(V) of the prototype Fe-TAML (decomposition at temperatures > À40 C) 33 leads to its conversion to the corresponding m-O-Fe IV 2 dimer, which is a much weaker oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] Recently, a [Fe III -TAML] (TAML ¼ tetra-amido macrocyclic ligand) 33 complex has been shown to oxidize activated benzylic C-H bonds via electrochemical formation of a dimeric m-O-Fe IV 2 intermediate in a divided cell. 34 The advantage of such electrochemical oxidation is that it eliminates the necessity of terminal oxidants like O 2 , H 2 O 2 , or mCPBA. In all these examples, the O-atom of water remains the source of the O-incorporation in the products.…”
Section: Introductionmentioning
confidence: 99%